Alternativas para el manejo de páramos en la Parroquia Pasa del cantón Ambato. - Fiallos Arcos, Victor Hugo (2010)
The present investigation was carried out in The Parish of Pasa that it is located in the western part of the County of the Tungurahua, at a distance of 17 kilometers of the city of Ambato, with the objectives of: To carry out the diagnostic agrosocioeconómico of the community, to identify the existent problems in relation to the handling of the moor of Raisin and to structure a plan of integral training for levels with a methodological support. The investigation was carried out with the directive of the different organizations that are the moor of the parish it Happens. For the I diagnose surveys they were structured that were applied the directive of 9 Town councils, Leaders of the organization of 2º grade, Comuneros of 9 base organizations, Directive of women's organization, members of the Parochial Meeting, Lideresas of the base organizations with an interviewed total of 120 that it corresponds to the total population's 10%. The information was analyzed obtained in field, for what a database will settle down in the program Excel. He/she was carried out the analysis and synthesis of the obtained primary information, he/she stops then to edit the I diagnose situational of the community with regard to the handling of the moor. Based on the problem found in the diagnose, an alternative proposal was elaborated for the handling of the moor of Pasa. The obtained results manifest that: 80.04% of the population of the communes of Raisin is between the 6 and 18 years, of which 55,04% is men and the 44,96 are women, near 26% of the residents it has finished the one of primary, 2% hardly has education of secondary and any inhabitant of the area had carried out university studies, the population's entrance average is of $190,02 dollars per month, the population's 88.98% is devoted to agricultural and cattle activities, of among the important cultivations those that the biggest percentage of farming crop is: Pope, trenches, beans, corn, carrot, barley and onion that the population of animals has diminished with relationship to previous years, the farmers of the parish Pass between 60 and 70% of the production you/he/she dedicates for the market, of the cattle products 97% of its production dedicates it for the sale. Inside the environmental aspects of the moor one has: that the water is diminishing and that for the future we will have very little or anything of water, the vegetation goes deteriorating with the lost of species and covered with the floor, good productions are not had and it is necessary to fertilize the floor to be able to cultivate, at the present time it has been entered to the moor, mainly bovine and equine in an excessive way, before they existed more animal wild in the moor and at the present time they exist few, the activities that the residents of the moor of Raisin carry out are highly of extraction, they don't carry out any activity for the conservation or protection of the moor; the main problem is the he/she burns of the straws and native vegetation of the moors, the second concern is the amplification of the agricultural frontier that one comes giving from the year 2000 and the third concern is the lack of classification of the moor. The alternatives that you/they suggest for the handling of the moor are: the use of a handling plan, training to the users and the regulation of the use of the moor. Based on that exposed it is recommended: the elaboration and/or correction and upgrade of the existent regulations of moor handling, in function of the necessities of conservation of the moor, the elaboration and implementation of a plan of handling of the moor, training and permanent technical attendance to the members of the community, to look for strategic alliances with institutions and organizations that cooperate in the goal of improving the conditions of the inhabitants' life and to carry out the conservation of the moors. As a result final you elaborates the plan of handling of the moor of Pasa.